Fast plasma production by intense femtosecond extreme ultraviolet and x-ray pulses - C. Fasolato; E. Stellino; F. Sacchetti; C. Petrillo (Physical Review Research)
We develop a semiempirical model to describe the creation of an electron plasma in matter at extreme conditions, as excited by high-intensity, extreme ultraviolet (EUV) or x-ray radiation pulses currently available at free-electron laser (FEL) facilities. In typical FEL experiments, EUV and x-ray pulses are used to investigate highly excited states of matter produced by optical pump pulses. The pump pulses, promoting electrons from delocalized valence band states, excite the system often through multiphoton absorption processes and/or shock wave propagation. Instead, the use of FEL radiation as a pump allows triggering electron transitions from bound, core states to nearly free levels above the Fermi energy, promptly generating a highly excited state, toward the warm dense matter regime. We model such an excitation process starting from the optical properties of the analyzed materials and first-principle considerations, with the aim of motivating further studies in this scheme. We apply our model to predict the differences in the plasma creation process in insulators and metals, at varying exciting pulse wavelength and fluence, and we interpret the results in terms of the different nature of the investigated systems. Furthermore, we explore the effect of the finite core hole lifetime on the plasma formation and relaxation dynamics. We show the model is suited for the interpretation of real experimental data obtained from a prototypical insulating crystal (LiF) in a EUV FEL pump–optical transmission probe experiment.